Factors minimizing propensity to create budgetary slack: empirical evidence in Indonesia - Kusuma, Budi Hartono (2016)
Budgetary slack is an example of dysfunctional behavior as a result of the participative budgeting process.Budgetary slack is the behavior of making underestimated revenue and overestimated cost.The purpose of budgetary slack is to make budget target easier to achieve and also to make the performance looks good.This research is conducted to prove the factors that empirically can minimize budgetary slack occurrence.This research wants to prove the influence of budgetary control and ethical work climate on budgetary slack and also want to prove the procedural justice perception as a mediating variable.Data used in this research is primary data which are collected using a survey through questionnaires to persons who have structural position in several private universities in Indonesia.Respondents were selected purposively to the lecturers and staffs with minimum of one year experience in structural position and actively involved in the budgeting process.Eightyeight questionnaires were accepted and used.The analysis technique used in this study is path analysis. This research reveals that the effectiveness of budgetary control through the mediation of procedural justice perception will minimize the propensity to create budgetary slack.This research also found the effectiveness of budgetary control and ethical work climate has positive influence on procedural justice perception. This research has no evidence to prove the negative influence on effectiveness of budgetary control and ethical work climate toward propensity to create budgetary slack. Procedural justice perception has no influence on propensity to create budgetary slack.The mediating effect of procedural justice perception on the influence of ethical work climate towards propensity to create budgetary slack could not been proved.The outcome of this research is employees need to be controlled in budgeting process with good procedural justice perception of subordinates to top management.